Political Movement and Civil Disobedience: Abstention Behavior of the Hindu-Buddhist Dayak Indigenous Community Bumi Segandu Indramayu - Wiji Febriyani Rizkiyah (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2024)
This research discusses political movements and civil disobedience which can be seen from the abstention behavior of the Bumi Segandu Indramayu Hindu-Buddhist Dayak Indigenous Community. This research aims to explain the behavior of the Bumi Segandu Indramayu Hindu-Buddhist Dayak Indigenous Community for abstention from the 2004 elections to the 2008 West Java regional elections and the factors that influenced it. This research uses descriptive research methods with a qualitative approach with ethnographic types. The results of this research reveal that the abstention behavior of the Bumi Segandu Indramayu Hindu-Buddhist Dayak Indigenous Community in Losarang District is a social movement that has developed into civil disobedience. There are two factors that influence the community's abstention, namely: 1) the existence of cultural values that influence the existence of the community, namely belief in nature which prioritizes elements of justice; and 2) the community's dislike for the conditions created during the New Order era until now. For this reason, the Bumi Segandu Indramayu Hindu-Buddhist Dayak Traditional Community dares to face all forms of challenges that oppose its existence and continues to carry out its activities with the aim of making their existence and form of existence acceptable to society.